Serotype distribution and antimicrobial susceptibility of Streptococcus pneumoniae isolates cultured from Japanese adult patients with community-acquired pneumonia in Goto City, Japan - Miyazaki, Taiga; van der Linden, Mark; Hirano, Katsuji; Maeda, Takahiro; Kohno, Shigeru; Gonzalez, Elisa N.; Zhang, Pingping; Isturiz, Raul E.; Gray, Sharon L.; Grant, Lindsay R.; Pride, Michael W.; Gessner, Bradford D.; et al. (Frontiers in Microbiology, 2024)
Streptococcus pneumoniae is an important cause of community-acquired pneumonia (CAP) in Japan. Here, we report the serotype distribution and antimicrobial susceptibility of cultured pneumococcal isolates from Japanese adults aged ≥18 years with CAP. This was a prospective, population-based, active surveillance study conducted in Goto City, Japan from December 2015 to November 2020. Pneumococcal isolates from sterile sites (blood and pleural fluid) and nonsterile sites (sputum and bronchoalveolar lavage) were cultured as part of the standard of care. S. pneumoniae were serotyped using the Quellung reaction. Antimicrobial susceptibility was tested using microdilution and interpreted according to the Clinical and Laboratory Standards Institute criteria. Isolates resistant to erythromycin were phenotyped using the triple-risk test and genotyped by polymerase chain reaction. A total of 156 pneumococcal isolates were collected (138 from sputum, 15 from blood, and 3 from bronchoalveolar lavage) from 1992 patients. Of these,142 were non-duplicate isolates from unique patients and were included in the analyses.Serotypes contained within the 13-valent pneumococcal conjugate vaccine (PCV13) (including 6C), PCV15 (including 6C), and PCV20 (including 6C and 15C) were detected in 39 (27%), 45 (32%), and 80 (56%) of 142 isolates, respectively. The most common serotypes were 35B (12%), 11A (11%), and 3 (11%). Multidrug resistance (MDR) was detected in 96/142 (68%) isolates. Of the 96 MDR isolates, 31%, 32%, and 59% were PCV13, PCV15, and PCV20 serotypes, respectively; the most common MDR serotypes were 35B (16%), 6C, 10A, and 15A (9% each), and 3 and 11A (8% each). A total of 119 isolates were resistant to macrolides; 41 (35%) had an M phenotype, 53 (45%) had an iMcLS phenotype, and 25 (21%) had a cMLS phenotype. In conclusion, pneumococcal serotypes 35B, 11A and 3 were most frequently associated with pneumonia and antimicrobial resistance was common among pneumococcal isolates from adults with CAP in Goto City, Japan. Implementing higher-valency PCVs may help reduce vaccinetype CAP among Japanese adults.